Enamel matrix derivative for replanted teeth in animal models: a systematic review and meta-analysis - Sahng G. Kim; Steven I. Ryu (Korean Academy of Conservative Dentistry, 2013)
Objectives To investigate the effect of enamel matrix derivative (EMD) on periodontal healing of replanted teeth in animal models. Materials and Methods The authors searched MEDLINE, PubMed, EMBASE, Cochrane Library, Web of Knowledge and Scopus for articles published up to Oct 2012. Animal studies in which EMD was applied in transplanted or replanted teeth with adequate controls and histological data were considered. Normal periodontal healing or root resorption determined by histology after EMD was applied in replanted teeth with adequate controls was used as outcome measures. The following search strategy was used: ('Emdogain' OR 'enamel matrix proteins' OR 'enamel matrix derivative') AND ('avulsion' OR 'transplantion' OR 'autotransplantation' OR 'replantation'). Results Six animal studies were included in the final review. There was great heterogeneity in study design among included studies. Two studies with similar study designs were identified and analyzed by a meta-analysis. The pooled estimates showed a significantly higher normal healing and surface resorption and significantly less inflammatory and replacement resorption in EMD-treated groups compared with non-EMD-treated groups. Conclusions With the limitations of this systematic review, the use of EMD led to greater normal periodontal healing and surface root resorption and less inflammatory and replacement root resorption in the presence of periodontal ligaments. However, no definite conclusion could be drawn with regard to the effect of EMD on periodontal healing and root resorption when no periodontal ligaments exist.